Developing Stem Cell-Based Therapies For Neural Repair - Lachlan Thompson (Frontiers Research Topics, 2015)
Current pharmacotherapies and surgical intervention provide limited benefit in the treatment of neural injuries or halting disease progression and has resulted in significant hope for the successes of stem cell research. The properties of stem cells render them appropriate for cell replacement therapy, endogenous repair, disease modeling as well as high-throughput drug screening and development. Such applications will aide in increasing our knowledge and developing treatments for neurodegenerative disorders such as Parkinson's disease and Huntington's diseases as well as neural traumas including ischemic brain damage and traumatic brain injury. This Frontiers Research topic encouraged contributions from the general field of stem cell biology, with a particular emphasis on utilizing these cells to develop new therapies for neural repair. Related articles deal with issues such as: breakthroughs in stem cell proliferation/differentiation methodologies, using pluripotent and neural stem cells for transplantation and endogenous repair, the use of patient derived stem cells for disease modeling, using stem cells for drug discovery as well as the ethical issues related to the use of stem cells.